Contribution of endophytes towards improving plant bioactive metabolites: a rescue option against red-taping of medicinal plants - Tsipinana, Sinawo; Husseiny, Samah; Alayande, Kazeem A.; Raslan, Mai; Amoo, Stephen; Adeleke, Rasheed (Frontiers in Plant Science, 2023)
Medicinal plants remain a valuable source for natural drug bioprospecting owing to their multi-target spectrum. However, their use as raw materials for novel drug synthesis has been greatly limited by unsustainable harvesting leading to decimation of their wild populations coupled with inherent low concentrations of constituent secondary metabolites per unit mass. Thus, adding value to the medicinal plants research dynamics calls for adequate attention. In light of this, medicinal plants harbour endophytes which are believed to be contributing towards the host plant survival and bioactive metabolites through series of physiological interference. Stimulating secondary metabolite production in medicinal plants by using endophytes as plant growth regulators has been demonstrated to be one of the most effective methods for increasing metabolite syntheses. Use of endophytes as plant growth promotors could help to ensure continuous supply of medicinal plants, and mitigate issues with fear of extinction. Endophytes minimize heavy metal toxicity in medicinal plants. It has been hypothesized that when medicinal plants are exposed to harsh conditions, associated endophytes are the primary signalling channels that induce defensive reactions. Endophytes go through different biochemical processes which lead to activation of defence mechanisms in the host plants. Thus, through signal transduction pathways, endophytic microorganisms influence genes involved in the generation of secondary metabolites by plant cells. Additionally, elucidating the role of gene clusters in production of secondary metabolites could expose factors associated with low secondary metabolites by medicinal plants. Promising endophyte strains can be manipulated for enhanced production of metabolites, hence, better probability of novel bioactive metabolites through strain improvement, mutagenesis, co-cultivation, and media adjustment.